Employers' recruitment and induction practices in selected European countries : An indirect measure of quality of the VET system? ; Paper presented at the European Conference on Educational Research (ECER) in Berlin, 13-16 September 2011 - Geiben, Marthe [Verfasser]; Grollmann, Philipp [Verfasser] (My University, 2011)
"The study INDUCT aims at discovering the relationship between the quality of a country's VET system and employers' recruitment and training practices. It is proposed that different types of educational systems lead to different forms of company-based recruitment, induction and training of novice employees. Information are gathered through a mixture of methods, i.e. survey and qualitative measures, addressing companies' recruitment and training practices in the Car Service and Business Administration sector. Four countries (United Kingdom, Spain, Finland and Germany) are participating in this feasibility study that aims at the development of an instrument for further use in large-scale transnational surveys. The countries were selected in order to capture a wide variety of VET systems. In this paper we discuss in how far induction time can be used as an indicator for the quality of a VET system across countries." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; T 1.5 International vergleichende Berufsbildungsforschung; Berufseinmündung; Zweite Schwelle; Berufsanfänger; Personalgewinnung; Einarbeitung; Fallstudie; Internationaler Vergleich; Bundesrepublik Deutschland; Vereinigtes Königreich; Spanien; Finnland